Soil Nutrient Status in Different Tea Gardens of Tinsukia District of Assam - Bordoloi, Arundhati; Sarmah, Amal Chandra; Pathak, Prasanna Kumar (International Journal of Economic Plants, 2021)
A field study was conducted to evaluate the effect of land use change from forest to tea cultivation on soil acidification as well as on soil parameters viz. organic carbon (OC), nitrogen (N), phosphorus (P) and potassium (K). A total of 120 surface soil samples (0–20 cm) were collected from the representative tea gardens of Tinsukia district, Assam, India. The soil acidification, organic carbon and nutrient concentration in soil at different fertilizer input levels i.e., high commercial fertilizer application (Jitani tea garden), low input commercial fertilizer+organic fertilizer (Agarwal Tea Garden) and organic fertilizer (Udayachal Tea Garden) and adjacent forest were measured in soil laboratory of Krishi Vigyan Kendra, Tinsukia. Tea cultivation caused soil acidification on increasing the application of chemical fertilizer. Lowest pH (3.1) was observed in soils of high commercial fertilizer application. Compared to the forest soil, significantly lower concentration of soil organic matter (0.35%) and nitrogen (207.56 kg ha-1) was observed in various tea plantations. Soil phosphorus was observed highest (45.76 kg ha-1) in organically treated soil as compared to forest soil and other two tea plantations. High potassium concentration (173.73 kg ha-1) was observed in chemically treated garden.